2020
DOI: 10.7150/jca.39722
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA CircHIPK3 Promotes Gemcitabine Sensitivity in Bladder Cancer

Abstract: Purpose: Recent studies showed circular RNA (circRNA) played important regulatory roles in tumors, including genesis of chemotherapy resistance. In this study, the role of circHIPK3 on chemotherapy resistance of bladder cancer (BC) will be clarified. Methods: Real-time quantitative PCR was applied to examine the circHIPK3 expression. The gemcitabine sensitivity and cell proliferation viability were analyzed by Cell Counting Kit-8 assay. Double-stained flow cytometry was used to detect the cell apoptosis. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“… 13 In the meantime, circRNAs have been indicated to be dysregulated in multiple cancer tissues relative to matched normal tissues, especially in BC, signifying their role as diagnostic and prognostic biomarkers of BC. 14 , 15 In the present work, a new circRNA, circ_0000629, was found remarkably downregulated in BC tissues and cells. We further revealed that circ_0000629 served as a tumor suppressor and had the potency to suppress the proliferation and aggressiveness of BC cells in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 56%
“… 13 In the meantime, circRNAs have been indicated to be dysregulated in multiple cancer tissues relative to matched normal tissues, especially in BC, signifying their role as diagnostic and prognostic biomarkers of BC. 14 , 15 In the present work, a new circRNA, circ_0000629, was found remarkably downregulated in BC tissues and cells. We further revealed that circ_0000629 served as a tumor suppressor and had the potency to suppress the proliferation and aggressiveness of BC cells in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 56%
“…circ-Foxo3 is derived from FOXO3 mRNA, and Cdr1as is formed by back-splicing of the cerebellar degeneration-related protein 1 gene ( 73 , 74 ). A different study illustrated that the overexpression of circHIPK3 has been shown to lead to an increased sensitization of BC cells to gemcitabine and act as a biomarker for DFS in patients with BC ( 75 ). In addition, the apoptosis and chemosensitivity of docetaxel in androgen-dependent PCa cells could be increased by the overexpression of circFoxo3.…”
Section: Circrnas Act As Therapeutic Targets For Bc Pca and Rccmentioning
confidence: 99%
“…Furthermore, circHIPK3 plays a regulatory role in metastasis in hepatocellular carcinoma (HCC) and glioma by sponging miR-338-3p and miR-124-3p, respectively. Then it induces the upregualation of EMT-associated proteins E-cadherin, N-cadherin, vimentin, and ZEB2, thus promoting EMT [ 39 , 87 89 ].…”
Section: Cellular Effects Caused By Circhipk3mentioning
confidence: 99%